Income Inequality and Well-Being in the U.S.: Evidence of Geographic-Scale- and Measure-Dependence - John Ifcher; Homa Zarghamee; Carol Lee Graham (Institute for the Study of Labor (IZA), 2016)
U.S. income inequality has risen dramatically in recent decades. Researchers consistently find that greater income inequality measured at the state or national level is associated with diminished subjective well-being (SWB) in the U.S. We conduct the first multi-scale analysis (i.e., at the ZIP-code, MSA, and state levels) of the inequality-SWB relationship using SWB data from the U.S. Gallup Healthways Well-Being Index and income inequality data from the American Community Survey. We use the rich set of well-being measures afforded by the dataset (evaluative, positive- and negative-affective hedonic, and health measures) to examine the consistency of the relationship. We find that the relationship is both scale-dependent and measure-dependent: income inequality is SWB-diminishing in large regions for all measures, SWB-diminishing in small regions for negative-affective hedonic measures, and SWB-improving in small regions for most other measures. Lastly, we find that taking all regions together, the net relationship between income inequality and SWB is negative.
Keywords: D3; I14; D6; 330; subjective well-being; income inequality; happiness; distribution of income; health; scale-dependence; measure-dependence